Embarrassment as a public vs. private emotion and symbolic coping behaviour - Soliman, Meikel (Frontiers in Psychology, 2024)
In dealing with embarrassment, individuals engage in symbolic coping behaviours (e.g., hiding one’s face by wearing sunglasses). Research investigated these behaviours when embarrassment is experienced as a public emotion (e.g., others present). Contrary, there is emerging evidence showing that embarrassment can be experienced as a private emotion (e.g., no others present) as well. This is why the present research seeks to enhance Dong et al.’s (2013) seminal work on symbolic coping behaviours and investigates to what extent symbolic coping behaviours differ when embarrassment is experienced in public and private. First, the present study finds that individuals experience embarrassment as a private as well as a public emotion. Second, both types of embarrassment relate to symbolic coping behaviours. Third, while both types of embarrassment experience a preference for face-hiding products there are differences in symbolic coping behaviours. Fourth, the study transfers Dong et al.’s (2013) research to a different cultural context.